Regulation of IgG antibody titers by the amount persisting of immune-complexed antigen. - Bachmann, M; Kündig, T; Hengartner, H; Zinkernagel, R (1994)
Antigens normally induce an immunoglobulin (Ig)G response which stays at an elevated level for several weeks or months, constituting an important part of the immunological memory. This study investigated factors influencing the level of neutralizing IgG titers against a virus and shows that within the range tested it was independent of the number of initially available and potentially responding T helper and B cells, but was regulated by the amount of specific IgG-immune complexes forming depots of persisting antigen. These findings support the notion that the efficiency of vaccines in inducing long-lasting protective IgG is regulated predominantly by the amount of persisting (and presumably follicular dendritic cell-associated) antigen-antibody complexes.